Analisis Kualitas Pelayanan pada Bagian Akademik Politeknik Sawunggalih Aji Purworejo - Yeni Kristiyan; Danis Imam Bachtiar (Universitas Wahid Hasyim, 2019)
In an educational institution, service is one of the most important things to note. Good service will be a satisfaction for the customer, in this case the students. Sawunggalih Aji Polytechnic is one of the colleges in Purworejo Regency. One of the core services in these colleges is academic services, where the main users are students. The services provided so far there are still some shortcomings related to physical aspects and human resources. To find out how the level of satisfaction of students with academic services is needed a study especially related to several factors including evidence of tangible, reliability, responsiveness, assurance and empathy. The research used was a questionnaire with multiple validity, reliability and linear regression analysis. Result of validity and reliability test, all items are declared valid because result of each test value rhitung> 0,279 and reliable because value of Alpha> 0,6. Regression result Y = 1,276 + 0,195 tangible + 0,093 reliability + 0,077 responsiveness + 0,508 emphaty + 0,340 assurance. In the F test (Anova) obtained Fcount of 31,426> Ftabel value which means that independent variable together effect to student's satisfaction. While in t test, the variable that has significant effect on student satisfaction is assurance variable with t count 2,953> from ttable value 2.015 and significance value equal to 0.005. Keywords: service, service quality.